Integration of Lampung Local Wisdom Values in Lampung History and Culture Lectures to Instill Student Nationalism - Cheri Saputra (International Journal of Educational and Life Sciences, 2024)
The many varieties of Lampung culture are an inseparable part of the Indonesian national culture that characterizes our Indonesia, meaning that if one of the cultures of this region is extinct and lost, our Indonesian national identity will naturally also disappear, because as we know that Indonesia is identified with many ethnic groups consisting of various elements and of course each of these ethnic groups has characteristic characteristics The characteristics of each so that it becomes a differentiator between one culture and another, so that it is the obligation of all children of the nation to preserve it both at the theoretical level and at the practical level. Nationalism itself is a form of love for the nation where he lives, therefore as a form of love for the country, it is required for every individual to know the forms and types of culture owned and preserve them by using them in daily life and interaction, if this is done by all components of the nation, then by itself the culture heritage of our ancestors will be preserved and become large and global, Especially today almost all components of the nation's children are familiar with the internet, especially the millennial generation who with their role who are now students have a very significant role and contribution to disseminate the culture of this region through their social media channels. This study aims to find out what are the forms of integration of Lampung local wisdom values that exist in Lampung history and culture lectures in order to instill nationalism attitudes of History Education Students of FKIP University of Lampung, while the method used in this study is a qualitative descriptive method, using this method it is hoped that it can explain and answer existing problems and challenges so as to obtain initial data on wisdom local integrated in Lampung history and culture lectures.